NATIONAL EDUCATION POLICY 2020: TOWARDS THE CREATION OF NEW INDIA: THE CHALLENGES AND POSSIBILITIES OF EDUCATION - Sharma, Dipika; Neha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
'Deshbhakti Dadati Rashtriyam L' (Bhagavad Gita) That is, patriotism leads to patriotism. "Vidya distribution science memory: readiness That is, "Vidya, logic, science, memory, readiness, and functionality, these six, nothing is incurable for the one who has." The importance and relevance of education can be understood by this formula. It cannot be denied that the level of education determines the foundation of any country. That is, the stronger the foundation is, the stronger and the internal strong. If you see the history of ancient India, then in India, when education was given through Gurukuls. At that time, the country was strong in the field of knowledge and in the economic field. This is the reason that India of that era was called the golden bird and the name of India was also the title of the world guru. The education system, which changed time and implemented by English, pushed India back to knowledge, but economically as well as intellectual sector. Now even if physical progress is visible, India is lagging behind in economic progress. After more than the year of independence, it was now conceived that the medium of education was approved. The foundation of India was strengthened since the long churn of the National Education Policy 2020.